2008
DOI: 10.1002/jor.20653
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic analysis of femoroacetabular impingement with Hip2norm—reliable and validated

Abstract: The purpose of this study was to validate the accuracy, consistency, and reproducibility/reliability of a new method for correction of pelvic tilt and rotation of radiographic hip parameters for pincer type of femoroacetabular impingement on an anteroposterior pelvic radiograph. Thirty cadaver hips and 100 randomized, blinded AP pelvic radiographs were used for investigation. To detect the software accuracy, the calculated femoral head coverage and classic hip parameters determined with our software were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(165 citation statements)
references
References 17 publications
9
155
1
Order By: Relevance
“…One of us not involved with the surgical care of the patients (SDS) assessed these images with the use of a validated software analysis program (Hip2Norm) [42,45,52]. This radiographic analysis provided parameters for proximal femoral and acetabular morphology and allows one to correct the measured parameters for malrotation of the pelvis during radiograph acquisition (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…One of us not involved with the surgical care of the patients (SDS) assessed these images with the use of a validated software analysis program (Hip2Norm) [42,45,52]. This radiographic analysis provided parameters for proximal femoral and acetabular morphology and allows one to correct the measured parameters for malrotation of the pelvis during radiograph acquisition (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…One observer (SDS) analyzed the individual acetabular morphologic features using validated computer software, Hip 2 Norm (University of Bern, Switzerland) [24,32]. The descriptive parameters were the LCE angle [30], acetabular [11].…”
Section: Patients and Materialsmentioning
confidence: 99%
“…The width (b) was measured perpendicular to the thickness (a). index [28], extrusion index [19], and femoral head coverage [24,25] (Table 1).…”
Section: Patients and Materialsmentioning
confidence: 99%
“…Some authors have reported on reliability and agreement of measures used in radiographic evaluation of the adult hip [2,9,16,28]. In these studies, the interobserver reliability was lower than the intraobserver reproducibility, and the ICC/kappa values for the parameters were various.…”
Section: Discussionmentioning
confidence: 99%